Proteomics of survival structures of fungal pathogens - Loginov, Dmitry; Šebela, Marek (New biotechnology, 2016)
•Proteins related to protein biosynthesis are prevalent in the dormant conidia.•Germination is a specific process in terms of protein regulation for each fungus.•Conidial surface proteins are new possible targets for antifungal drug screening. Fungal pathogens are causal agents of numerous human, animal, and plant diseases. They employ various infection modes to overcome host defense systems. Infection mechanisms of different fungi have been subjected to many comprehensive studies. These investigations have been facilitated by the development of various ‘-omics’ techniques, and proteomics has one of the leading roles in this regard. Fungal conidia and sclerotia could be considered the most important structures for pathogenesis as their germination is one of the first steps towards a host infection. They represent interesting objects for proteomic studies because of the presence of unique proteins with unexplored biotechnological potential required for pathogen viability, development and the subsequent host infection. Proteomic peculiarities of survival structures of different fungi, including those of biotechnological significance (e.g., Asperillus fumigatus, A. nidulans, Metarhizium anisopliae), in a dormant state, as well as changes in the protein production during early stages of fungal development are the subjects of the present review. We focused on biological aspects of proteomic studies of fungal survival structures rather than on an evaluation of proteomic approaches. For that reason, proteins that have been identified in this context are discussed from the point of view of their involvement in different biological processes and possible functions assigned to them. This is the first review paper summarizing recent advances in proteomics of fungal survival structures.